2000
DOI: 10.1007/s002460010103
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory Syncytial Virus in Patients with Congenital Heart Disease: A Contemporary Look at Epidemiology and Success of Preoperative Screening

Abstract: Awareness of respiratory syncytial virus (RSV) as a serious pathogen in the child with congenital heart disease is increasing. We studied the impact of RSV lower respiratory tract disease on patients in a large academic pediatric cardiology practice. We found that RSV disease necessitating hospitalization occurs in congenital heart disease patients well into the second year of life. Although pulmonary hypertension remains a significant risk factor for morbidity in these patients, it does not appear to be as mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
67
2
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(73 citation statements)
references
References 10 publications
3
67
2
1
Order By: Relevance
“…RSV infections typically cause mild illness, however severe disease can occur and is often associated with symptoms such as bronchiolitis and wheezing [6]. Populations at greatest risk to develop severe disease after RSV infection include premature infants [7], persons with congenital heart disease [8][9][10], immunocompromised individuals [11,12], and the elderly [11,13,14]. Clinical studies have indicated that children that are hospitalized due to RSV-induced disease exhibit an increased incidence of asthma later in life as compared to children that experience a mild or asymptomatic RSV infection (recently reviewed in [15]).…”
Section: Introductionmentioning
confidence: 99%
“…RSV infections typically cause mild illness, however severe disease can occur and is often associated with symptoms such as bronchiolitis and wheezing [6]. Populations at greatest risk to develop severe disease after RSV infection include premature infants [7], persons with congenital heart disease [8][9][10], immunocompromised individuals [11,12], and the elderly [11,13,14]. Clinical studies have indicated that children that are hospitalized due to RSV-induced disease exhibit an increased incidence of asthma later in life as compared to children that experience a mild or asymptomatic RSV infection (recently reviewed in [15]).…”
Section: Introductionmentioning
confidence: 99%
“…This is attributed to transient immunological dysfunction following cardiopulmonary bypass and possible dilution of serum neutralising antibodies Preoperative screening for asymptomatic RSV infection has been suggested as a way to reduce this morbidity. 13 The epidemiological evidence linking severe RSV LRTI to CHD begs an explanation and also warrants attempts to prevent severe disease in those infants and children.…”
Section: Rsv Infection In Chdmentioning
confidence: 99%
“…R espiratory syncytial virus (RSV) is the most common cause of lower respiratory tract infection in early childhood and leads to hospitalization in up to 2% of Canadian children younger than two years of age each winter (1). Children with hemodynamically significant cardiac disease may develop respiratory or cardiac failure during RSV infection, and have prolonged hospital stay, need intensive care and have higher mortality rates than healthy infants (2); they may also have worse postoperative clinical outcomes after corrective cardiac surgery (3,4). Seasonal prophylaxis with a humanized mouse monoclonal anti-RSV antibody (palivizumab, Abbott Laboratories, Canada) (5), reduces RSV-related hospitalization rates in children with hemodynamically significant heart disease, and Canadian authorities recommended in 2003 that eligible children be considered for passive immunization during the winter (6,7).…”
mentioning
confidence: 99%